Komersialisasi Pendidikan, Kesejahteraan Guru, dan Masa Depan Digitalisasi Pendidikan: (Tantangan dan Strategi Manajemen Sekolah Menuju Pendidikan Berkualitas Dan Inklusif) - Mochamad Fadillah; Robbiatul Amalia; Abdul Madjid Musannah; Purwaningrum Puji Lestari; Nunuk Indarti (Jurnal Pendidikan Indonesia, 2026)
Education is a strategic investment in human capital development and plays a vital role in promoting national competitiveness and sustainable development. However, contemporary educational systems face several critical challenges, including the commercialization of education, issues related to teacher welfare, and the rapid advancement of digital transformation. This article aims to analyze the relationship between educational commercialization and accessibility, examine the impact of teacher welfare on educational quality, and explore the future of educational digitalization in improving cost efficiency and school management effectiveness. This study employs a qualitative library research approach by reviewing relevant academic journals, policy documents, books, and recent research findings. The analysis reveals that educational commercialization can contribute positively to educational quality through improved facilities, innovative learning environments, and diversified funding sources. Nevertheless, it may also create inequalities in educational access, particularly for students from low-income families. Furthermore, teacher welfare is found to be a significant determinant of educational quality, as adequate financial and professional support enhances teacher motivation, job satisfaction, and instructional effectiveness. In addition, digitalization offers substantial opportunities for reducing operational costs, increasing administrative efficiency, and expanding access to learning resources. Despite these advantages, challenges such as digital infrastructure gaps, limited technological literacy, and unequal access to information technology remain significant concerns. Therefore, effective school management policies are required to balance educational quality, accessibility, teacher welfare, and technological innovation. The study concludes that sustainable educational development depends on an integrated management approach that promotes equity, professional teacher support, and strategic digital transformation to achieve inclusive and high-quality education.